ANALISIS PENDAPATAN ASLI DAERAH KABUPATEN SUBANG TAHUN 2017 -2019 - Fitriani Fitriani; Moeslihat Komara; Tepi Peirisal (Universitas Sultan Ageng Tirtayasa, 2021)
The study was based on revenue growth rate earring district within the last 3 years experience fluctuate. The level fluctuates due to un optional sources of local revenue. The purpose of this study is to analyze the local revenue of the Subang district from 2017 to 2019. The research method used is a qualitative method with a descriptive approach. The results showed that the growth rate of local revenue in Subang Regency has fluctuated. In addition, the level of financial independence earring districts classified as less well and still rely on government transfers in the context of financing for development and service to the community. Keywords: local revenue, local revenue growth, financial independence of local